2013
DOI: 10.1103/physrevb.87.180406
|View full text |Cite
|
Sign up to set email alerts
|

Role of the inter-sublattice exchange coupling in short-laser-pulse-induced demagnetization dynamics of GdCo and GdCoFe alloys

Abstract: The dynamics of the demagnetization induced by an ultrashort laser pulse in GdCo and GdCoFe alloys is shown to be substantially different from the expected trend. We find that the intersublattice exchange interaction between Gd and Co(Fe) is used as an additional route of heat transfer during the demagnetization process and leads to a temporary cooling of the Co(Fe) spin subsystem. The observed results are described by a four-temperature model (4T model) in which electrons, lattice, and 4f and 3d spins represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
31
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 28 publications
11
31
1
Order By: Relevance
“…Such two-step demagnetization dynamics, which includes a strong ultrafast component and a weak slower one within tens of picoseconds, is different from the typical one-step demagnetization dynamics of 3d spins in pure TMs like Fe and Co [1,20]. Similar two-step demagnetization dynamics of FeCo(Co) component were also reported in GdFeCo(GdCo) alloy films [26], where the second-step slower demagnetization process occurring within hundreds of picoseconds accounted for a large proportion in total demagnetization amplitude, and was attributed to lattice-spin(3d) coupling. However, here the amplitude of the first-step ultrafast demagnetization process seems absolutely dominant, and the timescale of the second-step demagnetization process is much shorter than the corresponding one in GdFeCo or GdCo.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Such two-step demagnetization dynamics, which includes a strong ultrafast component and a weak slower one within tens of picoseconds, is different from the typical one-step demagnetization dynamics of 3d spins in pure TMs like Fe and Co [1,20]. Similar two-step demagnetization dynamics of FeCo(Co) component were also reported in GdFeCo(GdCo) alloy films [26], where the second-step slower demagnetization process occurring within hundreds of picoseconds accounted for a large proportion in total demagnetization amplitude, and was attributed to lattice-spin(3d) coupling. However, here the amplitude of the first-step ultrafast demagnetization process seems absolutely dominant, and the timescale of the second-step demagnetization process is much shorter than the corresponding one in GdFeCo or GdCo.…”
Section: Resultssupporting
confidence: 55%
“…Recently, indirect evidence about the coupling between RE-4f and TM-3d demagnetization dynamics was reported. Mekonnen et al observed an anomalous two-step demagnetization dynamics of the TM component in GdCo and GdCoFe alloy films, and performed a calculation based on a four-temperature (4T) model, indirectly revealing the role of inter-atomic 3d-5d-4f exchange coupling on the demagnetization dynamics [26]. For further verification and clearer insight of the 3d-5d-4f coupling dynamics, direct observations of the 4f spin dynamics are very necessary.…”
Section: Introductionmentioning
confidence: 99%
“…This switching was explained within a general theoretical framework [Mentink et al ., 2012], and reproduced by both atomistic LLG [Ostler et al ., 2012] and the microscopic three-temperature model with two coupled spin baths [Schellekens and Koopmans, 2013b]. Further measurements on a -Gd-Fe-Co alloys support this interpretation [Mekonnen et al ., 2013; Hashimoto et al ., 2014; Medapalli et al ., 2014; Le Guyader et al ., 2015]. …”
Section: Interfacial Effects In Ultrafast Magnetization Dynamicsmentioning
confidence: 96%
“…In this context, it is also relevant to take note of the recently studied phenomenon of femtosecond-laser driven switching of magnetism in ferrimagnetic FeGdCo alloys that appears to rely on an ultrafast angular momentum transfer between nanoscale inhomogeneities 23–25 . Here, a key element of the physics behind this is the interaction of localized f moments and itinerant d electrons which show a different behavior in the transient state 26 . Recent x-ray diffraction measurements on elemental Ho have further explored this interaction in a system with magnetic order in both the 5d and 4f states but no net magnetic moment 27 .…”
Section: Incoherent Time-dependence: Statistical Subsystems In Thermamentioning
confidence: 99%